Computers helping people with special needs : 17th International Conference, ICCHP 2020, Lecco, Italy, September 9-11, 2020, Proceedings.: 17th International Conference, ICCHP 2020, Lecco, Italy, September 9-11, 2020, Proceedings. Part I (2020) - Unknown
No abstract available